IDENTIFICATION OF CANDIDA SPP. FROM CLINICAL SPECIMENS BY MATRIX-ASSISTED LASER DESORPTION/IONIZATION TIME-OF-FLIGHT MASS SPECTROMETRY (MALDI-TOF MS) - Suwannachote, Paphatchaya; Charoonwach, Wacharee; Phutphakwan, Khetsaraporn; Jamrassri, Pattaraporn; Khumsakulthai, Doungpat; Thanomsridetchai, Natthapaninee (Srinakharinwirot University Journal of Sciences and Technology, 2022)
Candida spp. is an important opportunistic fungus that can infect mainly in immunocompromised hosts, especially in HIV infected patients. Therefore, the accurate and rapid identification of Candida spp. is influential in treatment decision and may reduce the rate of antifungal drug resistance. The conventional methods of fungal identification in the clinical diagnostic laboratory are complicated and time-consuming. Matrix-Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) is one of rapid and reliable fungal diagnostic tools used nowadays. In this study, we evaluated eighty-five isolates of Candida spp. form clinical specimens by using MALDI-TOF MS technique compared to the conventional methods, including Germ tube test, Chlamydospore formation test and CHROMagar.The results demonstrated that MALDI-TOF MS technique can be used to differentiate Candida spp. from the clinical specimen especially for Candida glabrata, C. orthopsilosis, C. rugosa, Trichosporon asahii, and T. inkin which could not be previously identified by using conventional methods. From our study it can be concluded that MALDI-TOF MS technique is one of the accurate tools and appropriate to increase the efficiency of Candida identification.